The Etiology of Pneumonia in HIV-uninfected South African Children: Findings From the Pneumonia Etiology Research for Child Health (PERCH) Study. (September 2021) - Moore, David P.; Baillie, Vicky L.; Mudau, Azwifarwi; Wadula, Jeannette; Adams, Tanja; Mangera, Shafeeka; Verwey, Charl; Prosperi, Christine; Higdon, Melissa M.; Haddix, Meredith; Hammitt, Laura L.; Feikin, Daniel R.; et al.
Abstract : Background: Pneumonia is the major contributor to under 5 childhood mortality globally. We evaluated the etiology of pneumonia amongst HIV-uninfected South African children enrolled into the Pneumonia Etiology Research for Child Health case-control study. Methods: Cases, 1–59 months of age hospitalized with World Health Organization clinically defined severe/very severe pneumonia, were frequency-matched by age and season to community controls. Nasopharyngeal-oropharyngeal swabs were analyzed using polymerase chain reaction for 33 respiratory pathogens, and whole blood was tested for pneumococcal autolysin. Cases were also tested for Mycobacterium tuberculosis . Population etiologic fractions (EF) of pneumonia with radiologic evidence of consolidation/infiltrate were derived for each pathogen through Bayesian analysis. Results: Of the 805 HIV-uninfected cases enrolled based on clinical criteria, radiologically confirmed pneumonia was evident in 165 HIV-exposed, -uninfected, and 246 HIV-unexposed children. In HIV-exposed and HIV-unexposed children, respiratory syncytial virus was the most important pathogen with EFs of 31.6% [95% credible interval (CrI), 24.8%–38.8%] and 36.4% (95% CrI, 30.5%–43.1%), respectively. M. tuberculosis contributed EFs of 11.6% (95% CrI, 6.1%–18.8%) in HIV-exposed and 8.3% (95% CrI, 4.5%–13.8%) in HIV-unexposed children, including an EF of 16.3% (95% CrI, 6.1%–33.3%) in HIV-exposed children ≥12 months of age. Bacteremia (3.0% vs. 1.6%) and case fatality risk (3.6% vs. 3.7%) were similar in HIV-exposed and HIV-unexposed children. Conclusions: Vaccination strategies targeting respiratory syncytial virus should be prioritized for prevention of pneumonia in children. Furthermore, interventions are required to address the high burden of tuberculosis in the pathogenesis of acute community-acquired pneumonia in settings such as ours. Abstract : Supplemental Digital Content is available in the text.